Section of Poultry Pens - Frank Aston::::::photographer::: (1903)
Rear (west?) elevation of the poultry barn and poultry pens, chickens included. Published in the Polytechnic J. (May 1909) and the 1915-16 Bulletin, with caption 'Prize Winning Poultry.'